The occurrence of specific invaginations (eizosomes) in the yeast cytoplasmic membrane as a result of secretory processes: a new version - Dmitriev, Vladimir V.; Rusakova, Tatyana G.; Machulin, Andrey V.; Farofonova, Vasilina V.; Zvonarev, Anton N. (Experimental Biology and Biotechnology, 2023)
Based on cytobiochemical and morphometric data, a significant variability in the morphology of the plasmalemma in yeast in different physiological situations was shown for the first time. Three types of adaptive structural and functional rearrangements of the plasmalemma were found. Ultrastructural changes in the plasma membrane and cell wall of Candida maltosa, Cryptococcus humicola and Saccharomycopsis lipolytica, occurring with the consumption of hexadecane, the surfactant laurox-9 and olive oil respectively, were studied using electron microscopic cytochemistry and cryofractography. It was shown that in the first hours of incubation (lag phase), specific structures appear in the cytoplasmic membranes of these yeasts: spherical invaginations in C. maltosa, pocket-like invaginations in Cr. humicola and ordinary invaginations in S. lipolytica. With further cultivation, all these invaginations either underwent structural changes or disappeared. We assume that the appearance of these structures is associated with an increase in the area of the cytoplasmic membrane due to the inclusion of membranes of secretory vesicles. An interesting discovery was the fact that modified sections of the cell wall, which we previously described as canals, were also observed in opportunistic yeast species C. albicans and C. tropicalis when growing on hydrocarbons. The data obtained not only expand the understanding of the adaptive rearrangements of yeast cells, but may also be of practical importance, namely, in the treatment of mycoses caused by yeast organisms.
Keywords: yeast cytoplasmic membrane; invaginations; electron microscopy; cryofractography; cytochemistry